Development of a Machine Learning Model to Predict the Corrosion Inhibition Ability of Benzimidazole Compounds - Aprilyani Nur Safitri; Gustina Alfa Trisnapradika; Achmad Wahid Kurniawan; Wahyu AJi Eko Prabowo; Muhamad Akrom (Journal of Multiscale Materials Informatics, 2024)
The purpose of this study is to use quantitative structure-property relationship (QSPR)-based machine learning (ML) to examine the corrosion inhibition capabilities of benzimidazole compounds. The primary difficulty in ML development is creating a model with a high degree of precision so that the predictions are correct and pertinent to the material's actual attributes. We assess the comparison between the extra trees regressor (EXT) as an ensemble model and the decision tree regressor (DT) as a basic model. It was discovered that the EXT model had better predictive performance in predicting the corrosion inhibition performance of benzimidazole compounds based on the coefficient of determination (R2) and root mean square error (RMSE) metrics compared DT model. This method provides a fresh viewpoint on the capacity of ML models to forecast potent corrosion inhibitors.